2021
DOI: 10.3389/fneur.2021.700166
|View full text |Cite
|
Sign up to set email alerts
|

Early Predictors of the Increase in Perihematomal Edema Volume After Intracerebral Hemorrhage: A Retrospective Analysis From the Risa-MIS-ICH Study

Abstract: Background and Purpose: Perihematomal edema (PHE) is associated with poor functional outcomes after intracerebral hemorrhage (ICH). Early identification of risk factors associated with PHE growth may allow for targeted therapeutic interventions.Methods: We used data contained in the risk stratification and minimally invasive surgery in acute intracerebral hemorrhage (Risa-MIS-ICH) patients: a prospective multicenter cohort study. Patients' clinical, laboratory, and radiological data within 24 h of admission we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 23 publications
1
20
0
Order By: Relevance
“…Meanwhile, data from the Intensive Blood Pressure Reduction in Acute Cerebral Haemorrhage Trial (INTERACT) indicated that a history of hypertension, baseline hematoma volume, body temperature, and time from the onset of symptoms to CT scan were independently associated with a relative increase in PHE in 207 patients with acute ICH [ 138 ]. In particular, many studies implied that a large volume of ICH was correlated with the severity and progression of PHE [ 115 , 116 , 138 , 139 ]. Probably due to the ambiguous effects of fever on ICH outcomes, the effects of therapeutic hypothermia on brain edema are currently heterogeneous in patients with ICH [ 123 , 140 , 141 ].…”
Section: Factors That May Impact Phementioning
confidence: 99%
See 4 more Smart Citations
“…Meanwhile, data from the Intensive Blood Pressure Reduction in Acute Cerebral Haemorrhage Trial (INTERACT) indicated that a history of hypertension, baseline hematoma volume, body temperature, and time from the onset of symptoms to CT scan were independently associated with a relative increase in PHE in 207 patients with acute ICH [ 138 ]. In particular, many studies implied that a large volume of ICH was correlated with the severity and progression of PHE [ 115 , 116 , 138 , 139 ]. Probably due to the ambiguous effects of fever on ICH outcomes, the effects of therapeutic hypothermia on brain edema are currently heterogeneous in patients with ICH [ 123 , 140 , 141 ].…”
Section: Factors That May Impact Phementioning
confidence: 99%
“…The growth of PHE measured by PHE expansion and EED was also used to evaluate the severity of brain edema after ICH in patients. Two clinical studies have found that an increase in absolute PHE volume from baseline to day 3 was correlated with a poor outcome 3 months after ICH [ 116 , 179 ]. A study with 115 patients also found that the PHE expansion rate from baseline to 72 hours was associated with poor functional outcomes after deep ICH [ 180 ].…”
Section: Phe and Functional Outcomesmentioning
confidence: 99%
See 3 more Smart Citations